Systemic Inflammation Increases the Susceptibility to Levodopa-Induced Dyskinesia in 6-OHDA Lesioned Rats by Targeting the NR2B-Medicated PKC/MEK/ERK Pathway - Yan, Aijuan; Song, Lu; Zhang, Yu; Wang, Xijin; Liu, Zhenguo (Frontiers in Aging Neuroscience, 2021)
Abstract: Background: Long-term administration of levodopa, the gold-standard treatment for PD, is irreparably associated with levodopa-induced dyskinesia (LID), that dramatically affects patients’ quality of life. However, the underlying molecular mechanisms of how LID exacerbates remain unknown. Neuroinflammation in the striatum plays an active role in LID. These findings prompt investigation of non-neuronal mechanisms of LID. Our study will examine the effects of systemic inflammation in the development and progression of LID. Methods: To evaluate the possible influence of systemic inflammation in the appearance of LID, PD rats received an intraperitoneal injection of various concentrations of lipopolysaccharide (LPS, 1, 2, 5 mg/kg) or saline. One day later, these PD rats started to receive a daily treatment with L-dopa (6 mg/kg) plus benserazide (6 mg/kg) or saline for 21 days, and dyskinesia were evaluated at several time-points. Moreover, the activation of microglia and astrocyte, as well as molecular changes in NR2B and mGLUR5 signaling pathways were measured. Results: We found that systemic inflammatory stimulation with LPS exacerbated the intensity of abnormal involuntary movements (AIMs) induced by L-dopa treatment in 6-Hydroxydopamine (6-OHDA) lesioned rats. The LPS injection activated the gliocyte and increased the levels of pro-inflammatory cytokines in the striatum in LID rats. PD rats which received injection of LPS showed over-expression of p-NR2B and NR2B, as well as activated PKC/MEK/ERK and NF-κB signal pathways in response to L-dopa administration. On the contrary, clodronate encapsulated in liposomes (Clo lipo), which could suppress the inflammatory response induced by peripheral LPS injection, improved behavioral dysfunction, inhibited neuroinflammation, prevented NR2B over-expression and decreased the phosphorylation of PKC/MEK/ERK and NF-κB signaling pathways. Conclusion: This study suggests that systemic inflammation, by exacerbating preexisting neuroinflammation and facilitating NR2B subunit activity, may play a crucial role in the development of LID. Clodronate liposome administration restores the effects of LPS and decreases the susceptibility to L-dopa induced dyskinesia in 6-OHDA lesioned rats.